The Influence of Tax Understanding, Taxpayer Awareness and the E-Samsat System in the Covid-19 Era on the Implementation of Motor Vehicle Tax Payments Instructions in Sidoarjo: Pengaruh Pemahaman Pajak, Kesadaran Wajib Pajak dan Sistem E-Samsat di Era Covid-19 Terhadap Implementasi Petunjuk Setoran Pajak Kendaraan Bermotor di Sidoarjo - Safrida, Harli Aulia (Indonesian Journal of Law and Economics Review, 2022)
This study aims to clarify and understand the meaning of taxation, taxpayer awareness and the use of the ESamsat system for payment of vehicle taxes in the Sidoarjo area during the covid19 pandemic. This research is based on motor vehicle tax revenues that are not yet optimal. This research method uses quantitative data collection by distributing 100 questionnaires to respondents from all vehicle taxpayers in the Sidoarjo area. This study states that the results of tax understanding (X1) have a positive effect on the implementation of vehicle tax payments (Y) and taxpayer awareness (X2) has a negative effect on the implementation of vehicle tax payments (Y) and the E-Samsat system in the Covid19 era (X3). positive effect on the implementation of motor vehicle tax payments (Y).